The Usefulness and Ease of Use of WAP Application For Local Agriculture Product - Elaish, Monther Mustafa Abubaker (2008)
Mobile devices and the appearance of wireless technology are rapidly increasing. However, the benefits of mobile applications to rural people particularly are not as obvious. This study identified and designed a WAP-based Agriculture seller system using WAPtor and MySQL. This study has included results of three questionnaires for knowing extend of technology among the agriculture field. This study also has used the prototype to measure and compares the acceptance of use between two different groups' seller of Changlun and student of Kolej Pertanian Malaysia to know the acceptance of technology. The results showed that the fruit sellers and framers in Changlun have not benefit from WAP technology as most of them have education below SPM. The study also shows that level education had improved the knowledge and the willingness of the use of technology as expected.